In Vitro Activity and In Vivo Efficacy of Posaconazole in Treatment of Murine Infections by Different Isolates of the Aspergillus terreus Complex - Salas, Valentina (American Society for Microbiology (ASM), 2011)
Posaconazole (PSC) is an antifungal drug recommended as an alternative for the treatment of invasive aspergillosis in patients who are refractory or intolerant to primary antifungal therapy. We have evaluated the in vitro activity of PSC against 21 strains of the Aspergillus terreus complex using both broth microdilution and disk diffusion (Neo Sensitabs) methods. PSC showed the same high level of activity against all the strains with the two in vitro methods used. We developed a murine model of disseminated infection to evaluate the efficacy of PSC at 5, 10, or 20 mg/kg of body weight twice a day by using 6 different strains chosen randomly. PSC showed good efficacy, especially at 20 mg/kg, as measured by prolonged survival, tissue burden reduction, histopathology, and lowered galactomannan levels. The PSC levels in serum on the fourth day of treatment were higher than the MICs for the strains tested.